Asymmetries in the capital structure speed of adjustment: The idiosyncratic case of the maritime industry - Ioannis Chasiotis; Dimitrios Konstantios; Vassilios-Christos Naoum (Cogent Economics & Finance, 2022)
This study investigates asymmetries in the capital structure speed of adjustment in the case of a capital-intensive industry. Employing a sample of globally listed maritime, manufacturing and services firms between 1995 and 2020, we estimate a regime-switching partial adjustment model, to test whether the capital structure speed of adjustment depends on a firm's positioning relative to the target. After accounting for the fractional, bounded nature of leverage ratios using a DPF estimator we document that maritime firms exhibit a higher (lower) speed of adjustment when they lie below (above) their target. Our empirical findings suggest that this asymmetric behavior holds across industries but is more profound in maritime firms emphasizing this industry's particularity.
Keywords: G32; 330; capital structure; speed of adjustment; trade-off theory; maritime industry; service industry; manufacturing industry